Motivasi Atlet Maluku Pada PON KE XX Tahun 2021 Di Papua - Loklomin, Lamrat; Hasbullah, Bahmid; Rumahlewang, Emma (MANGGUREBE: Journal Physical Education, Health and Recreation, 2023)
Based on the background, the problem formulation in this research is: Motivation is important for Maluku athletes in 2021 at PON XX Papua. This research aims to find the level and motivation of Maluku athletes in 2021 at PON XX Papua. This research use to quantitative type. It's aims to describe, record, and quantitatively analyze existing conditions. This variable is a single, namely the motivation of Maluku athletes in realizing achievements. Thus the motivation of Maluku athletes in 2012 at PON XX Papua. the indicator of intrinsic motivation is more high category, 65.12% or 28 athletes, the indicator of extrinsic motivation is more high category, 58.14%. or 25 athletes. Based on the explanation above, the researchers knows that the indicators of intrinsic motivation and extrinsic motivation are more high category.